Customer focused optimal design skill training module from the informatics perspective - Zakaria, Anies Faziehan (2020)
Design informatics refers to the processing and application of information in the design process. In the case study of Product-Service Bundle (PSB), design analysis has become challenging due to the increasing amount of complex design information. Given such a design complexity, there are challenges in term of technical and educational needs of data-driven design. Therefore, a design skill training module of customer-focused optimal design was proposed. This study was conducted based on four main parts: (a) Part I: The Customer Knowledge Discovery (conjoint analysis and decision tree method); (b) Part II: The PSB Design and Optimisation (multiobjective optimisation technique); (c) Part III: The Design and Development of Training Modules (ADDIE Model) with Experts Validation (n=5); and (d) Part IV: The User Study of Skill Training Module (n=21). As results, in Part I the generated rules for product-service that matching the product and service features were identified. Part II, two case studies that show new PSB pricing reference based on existing offers were illustrated. Then, four modules of customer-focused optimal design training were developed in Part III and the average of expert’s validation score, 70%-85% were obtained which exceeding the suggested acceptable threshold, 70%. Finally, an increment of trainees achievement that obtained ‘A’ grade in each training was recorded in Part IV; 23.81%, 28.57%, 38.10%, and 61.90%, respectively. Besides, the frequencies of trainee’s achievement grades were presented based on demographic profiles; (i) working experiences, with (n=3), without (n=13), and training (n=5); (ii) level of skills; basic (n=6), intermediate (n=12), advanced (n=3), respectively. Lastly, the feedback of post-training survey presented good usability rating and feasibility of the suggested training modules. In conclusion, this study provides one of the potential solutions for solving design issues that can be applied in engineering education.